If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x=-5(x+1)-x
We move all terms to the left:
-6x-(-5(x+1)-x)=0
We calculate terms in parentheses: -(-5(x+1)-x), so:We get rid of parentheses
-5(x+1)-x
We add all the numbers together, and all the variables
-1x-5(x+1)
We multiply parentheses
-1x-5x-5
We add all the numbers together, and all the variables
-6x-5
Back to the equation:
-(-6x-5)
-6x+6x+5=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation
| 2x+7=175 | | 9x+10+7x-6=180 | | y-30+y-13=y+28 | | -1x-9=-3x | | 3g-(4g-6)=34 | | 5t+10-6t+1=-2 | | (x+5)/4=-10 | | 4x-19=8x+5 | | 18=9-a | | -2(9y-5)=-25-4y | | 5-2i+3+7i=0 | | (1.07^x)=1000 | | 7x=42* | | 5-2i-3+7i=0 | | x+180=35 | | 12/x=1+12/(x+1) | | 2(x+2)=4(x-12) | | 3x+2+2x-1=33 | | (12/x)-(12/(x+1))=1 | | -8-x=3x+6 | | (5-2i)+(3+7i)=0 | | 2x-9+6=15 | | 4x+1=11x-3 | | |r/4|=3 | | 60°8x-4=180 | | n-12.1=23 | | 4y^2+12y=7 | | b+40=12b-48 | | 4(p+1)=64 | | f+52.8=75 | | 3/y=81 | | 4(k-6=20 |